An integrated marketing communications campaign for Slim 'n White - Bantugon, Karen Michelle (Animo Repository, 2009)
The dietary supplements over-the-counter product category is a 1.93B industry with 63.50% annual growth in 2007. About 47.80% or 022.54M are positioned as beauty supplements during this year. Among the beauty supplements, the leading brands are positioned as health products while market followers as beauty products. Emotional positioning is also being used by recent market followers. In general, Filipinos hope to have white skin and slim body to feel their self-worth. Specially, the female young professionals are found to lead an unhealthy lifestyle. A more serious condition us chronic energy deficiency, a sustained period of lacking of energy among adults women. This group is aiming to achieve a work-life balance to no to miss out on most important things in life. Slim 'n White, the subject of this campaign, is classified as a beauty supplement with 0.52% market share. It is positioned as both a beauty and health combined product by the company. Sales had risen in 2009 to an average of 750, 000 a month when BFAD approval was secured. Product effectiveness of the 2 main beauty ingredients, Glutathione and I-carnitine, will take some time and effort from the consumer before it can be visible. Meanwhile, an additional burst of energy can be felt by the consumer taking Slim 'n White due to its Chromium Picolinate ingredient. In brief, Slim 'n White had failed to communicate a clear positioning statement when it used multiple positioning and mixed messages across its communications. This also resulted to a brand identify easily copied by competitors. Meanwhile, consumers receive multiple benefit communications either as slimming, whitening or both. The recommended strategy is to re-launched the brand as Slim 'n White Novae with C-Picolinate, an energy booster, as the key differentiator among the beauty supplements. The brand will be the known advocate of active lifestyle for the female yuppies who needs energy to achieve. Communications across channels will move them into action and/or conviction to take charge of their work-life balance.